Optimizing IT Support Operations with Web Development at PT Global Loyalty Indonesia - Istiono, Wirawan; Rianto, Dwi (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
IT Support at the company PT Global Loyalty Indonesia is considered to have less effective performance and often does repetitive work, such as several problems that have been resolved before that require a lot of experiments, when the same thing happens on a different day, the time-consuming experimental actions will be carried out again, so that the completion of the work takes a long time, this is because there is no recording of the steps that have previously been carried out. In addition, work requests to IT Support are only done verbally without detailed data collection, besides that ineffective standard operating procedures make IT Support employees confused when problems occur that have never been experienced before, so the work process takes a long time. To overcome these problems, a website system was created using HTML, CSS, React JS and Bootstrap with the Agile development method. After the website was completed and applied to the IT Support section, it was obtained from the results of interviews by the head of IT Support, that the work in the section became more organized, more recorded and easier to monitor by the head of IT Support, besides that it was also stated by the head of IT Support that the website created was very helpful and made IT Support work easier, with an average user acceptance of 86.4% which was calculated using the user acceptance test method